Unveiling the Hidden Gem: An Observational Report, Taxonomic Insights and First Photographic Evidence of Pseudochazara baldiva Moore, 1865, from India (Lepidoptera: Nymphalidae) - Lovish Garlani (SHILAP, 2024)
A field survey of the Spiti and Pin Valley of Himachal Pradesh in September 2023 revealed the presence of Pseudochazara baldiva Moore, 1865 in the region. In the earlier studies recently conducted in the region, the species is believed to have been misidentified by many authors as Pseudochazara lehana Moore, 1878. The identification of the species was done based on the phenotypic description given in Moore (1865), Evans (1932), and Talbot (1947). The study also provides the first photographic evidence of Pseudochazara baldiva Moore, 1865, from the region